Peran Komunikasi Korporat dari PT Angkasa Pura I dalam mengimplementasikan Strategi Media Relations - Pradana, Nicholas Jevan; Primadini, Intan (Soetomo Communication and Humanities, 2021)
The airport is no longer just a place for planes to land and depart, but has also become a destination. Yogyakarta International Airport is a new airport that replaces Adisutjipto International Airport. At the beginning of construction, Yogyakarta International Airport was opposed by both the local community who felt that the land was taken to be used as an airport, as well as the people of Yogyakarta who were used to going to Adi Sutjipto airport which is very close (ten to fifteen minutes away) compared to the new airport in Kulon Progo which requires an hour or an hour and a half to reach the destination. To overcome the problem, Corporate Communication PT. Angkasa Pura I implemented a media relations strategy, which involved journalists and the media, to restore its image. The concept used is Iriantara's media relations strategy which consists of managing relationships, developing relationship strategies, and developing networks. This research uses a post-positivistic paradigm and a qualitative approach, with a case study method. The results obtained in this research are that PT Angkasa Pura I has implemented a media relations strategy with the media, the media community and media organizations. The media relations strategy was carried out by distributing press releases, conducting media gatherings, media visits, media tours and media monitoring.